Transcranial Direct Current Stimulation for Patients With Pharmacoresistant Epileptic Spasms: A Pilot Study - Yang, Dongju; Du, Qiaoyi; Huang, Zhaoyang; Li, Liping; Zhang, Zhang; Zhang, Liping; Zhao, Xin; Zhao, Xuan; Li, Ting; Lin, Yicong; Wang, Yuping (Frontiers in Neurology, 2019)
Background: Epileptic spasms (ES) is a severe seizure type and lack of adequate methods for controlling of clinical attacks. Previous studies have indicated that cathodal transcranial direct current stimulation (tDCS) reduces seizure frequency for patients with epilepsy. ES are proposed to have a focal cortical origin. We hypothesized that patients with ES exhibit hyperactive network hubs in the parietal lobe, and that cathodal tDCS targeting the bilateral parietal region can reduce seizure frequency in patients with pharmacoresistant ES. Materials and Methods: The present study consisted of three basic phases: (a) a pre-treatment monitoring period for 14 days; (b) a consecutive 14-day treatment period during which patients were treated with 1 or 2 mA cathode tDCS for 40 minutes once per day; (c) and a follow-up period for at least 28 days. During the first 20 minutes of treatment, the cathode was placed over the right parietal lobe (P4) with the reference electrode over the contralateral supra-orbital area. In the second 20 minutes, the cathode was placed over the left parietal lobe (P3), with the reference electrode over the contralateral supra-orbital area. All patients received active tDCS treatment, and some patients underwent more than one treatment block. Patients maintained a seizure diary throughout the study. Antiepileptic drug therapy remained unchanged throughout the study. K-related samples Friedman tests and two-related samples tests were used to analyze data from all patients. Results: Seven patients with pharmacoresistant ES were included, receiving a total of eighteen 14-day blocks of tDCS treatment. We observed a significant difference in seizure frequency at the second month (p=0.028, unadjusted), as well as a trend towards decreased seizure frequency at the fourth month (p=0.068, unadjusted) of the first follow-up, relative to baseline. Three of seven patients (42.9%) exhibited sustained seizure reduction, while one (14.3%) experienced a short-term reduction in seizure frequency following cathodal tDCS treatment. Treatment was well tolerated in all patients. Conclusions: Repeated tDCS with the cathode placed over the bilateral parietal region is safe and may be effective for reducing seizure frequency in a subgroup of patients with pharmacoresistant ES.